PENGARUH PEMBERIAN SARI KACANG MERAH TERHADAP PENINGKATAN HEMOGLOBIN PADA REMAJA PUTRI - Harahap, Novy Ramini; Rauda, Rauda; Tampubolon, Ida Lestari; Lubis, Yurika Chindi (Universitas Murni Teguh, 2025)
Hemoglobin is an essential component of blood that functions to transport oxygen and iron throughout the body’s tissues. A deficiency in hemoglobin below the normal range can lead to anemia. Preventive efforts can be carried out through the administration of iron supplements and the consumption of iron-rich foods, such as red beans. This study aims to determine the effect of red bean extract on increasing hemoglobin levels among adolescent girls at SMP Amanah 1 Medan. The study employed a quasi-experimental design with a one-group pretest–posttest approach. The study population consisted of all female students at SMP Amanah 1 Medan, totaling 33 individuals. The sample was selected using purposive sampling, resulting in 10 adolescent girls as respondents. Data were collected using an observation sheet and analyzed univariately and bivariately using the paired sample t-test with a significance level of α = 0.05. The average hemoglobin level before the administration of red bean extract was 11.34 g/dL, which increased to 11.99 g/dL after the intervention. The paired sample t-test showed a p-value of 0.000 < 0.05, indicating a significant difference before and after the administration of red bean extract. The findings conclude that red bean extract has an effect on increasing hemoglobin levels among adolescent girls at SMP Amanah 1 Modern Medan. It is recommended that the school provide education on anemia and its prevention, as well as offer foods or beverages made from red beans in the school cafeteria. Abstrak Hemoglobin merupakan komponen penting dalam darah yang berperan membawa oksigen dan zat besi untuk disalurkan ke seluruh jaringan tubuh. Kekurangan hemoglobin di bawah batas normal dapat menyebabkan anemia. Upaya pencegahan dapat dilakukan melalui pemberian tablet tambah darah serta konsumsi makanan tinggi zat besi, salah satunya kacang merah. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian sari kacang merah terhadap peningkatan kadar hemoglobin pada remaja putri di SMP Amanah 1 Medan. Penelitian menggunakan desain quasi-experiment dengan pendekatan one group pretest–posttest. Populasi penelitian terdiri dari seluruh siswi SMP Amanah 1 Medan sebanyak 33 orang. Sampel dipilih dengan teknik purposive sampling sehingga diperoleh 10 remaja putri sebagai responden. Data dikumpulkan menggunakan lembar observasi dan dianalisis secara univariat serta bivariat menggunakan uji paired sample t-test dengan tingkat signifikansi α = 0,05. Rata-rata kadar hemoglobin sebelum pemberian sari kacang merah adalah 11,34 gr/dL, dan meningkat menjadi 11,99 gr/dL setelah intervensi. Hasil uji paired sample t-test menunjukkan nilai p = 0,000 < 0,05, yang menandakan adanya perbedaan signifikan sebelum dan sesudah pemberian sari kacang merah. Terdapat pengaruh pemberian sari kacang merah terhadap peningkatan kadar hemoglobin pada remaja putri di SMP Amanah 1 Modern Medan. Disarankan kepada pihak sekolah untuk memberikan penyuluhan mengenai anemia dan pencegahannya serta menyediakan makanan atau minuman berbahan dasar kacang merah di kantin sekolah.